EVALUASI KEBIJAKAN PERATURAN BUPATI NOMOR 7 TAHUN 2013 TENTANG PEDOMAN DAN TATACARA PELAYANAN MEDIK RUMAH SAKIT UMUM DAERAH KABUPATEN MALINAU SEBAGAI RUMAH SAKIT RUJUKAN - Melani Indah Pudjiastuti; Adam Idris; Aji Ratna Kusuma (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
This study aims to evaluate the policy of the Regent of Malinau Number 7 of 2013 on Guidelines and Procedures for Medical Service of Malinau District General Hospital as Referral Hospital. This study uses a descriptive quantitative approach with a view to obtaining an in-depth description of the incentive package policy evaluation. The data obtained were surveyed by questionnaires, observations, and data from Malinau District Hospital, which was then analyzed. The results of the research indicate that the incentive regulation policy stated in the Regent of Malinau Regulation No. 7 of 2013 on Guidelines and Procedures of Medical Service of Malinau District General Hospital as Referral Hospital has not been running well because of the six dimensions of Dunn's Evaluation Policy version there is one that has not yet fulfilled ie Dimension Efficiency.Keywords: Evaluation, Policy, Services